Optimalisasi Penentuan Kriteria Siswa Kelas Unggul dengan Metode Simple Additive Weighting - Khairunnisa, K (Journal of Research and Investigation in Education, 2023)
Education has an important role that is very decisive, not only for the development and realization of individuals but also for the development of the nation and state. This relates to the same quality of education and must be provided to Indonesian citizens, both normally and differently. The process of class division every new academic year is usually still carried out conventionally, namely by means of the sorting method and does not involve intelligent system technology. Therefore, not all students who enter the superior class have the desired criteria. The use of a Decision Support System (DSS) is expected to help the decisions made in selecting and determining who is the best student, considering that so far no particular method has been used in selecting students so that sometimes decisions are considered less objective and not on target. This decision support system using the simple additive weighting (SAW) method is processed with data sourced from student data at SMP Negeri 25 Padang. This research was conducted by finding the weight value for each attribute, then a ranking process was carried out that would determine the optimal alternative, namely the best students. Based on the analysis of the decision support system with this method is done by taking 3 criteria, namely the criteria for attitudes, criteria for value and criteria for ranking. Where the results of the researcher are the rankings that can support the best decisions for the criteria of superior class students. From the researcher, it can be concluded that the best students have high attitude criteria, high scoring criteria, and high ranking criteria. Based on the data that has been researched, there are students who score Exelia Monica with code A5 having a value of 3.